2022
DOI: 10.3389/fcell.2022.820286
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast Differentiation Affects Crucial Nutritive Functions of Placental Membrane Transporters

Abstract: Cytotrophoblasts are progenitor cells that proliferate and fuse to form the multinucleated syncytiotrophoblast layer, implicated in placental endocrine and transport functions. While membrane transporters play a critical role in the distribution of nutrients, hormones, and xenobiotics at the maternal-fetal interface, their selectivity to the syncytiotrophoblast layer is poorly characterized. We aimed to evaluate the regulation of placental transporters in response to trophoblast differentiation in vitro. Exper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that the trophoblast differentiation process is associated with simultaneous induction and repression of numerous genes that encode functionally related proteins [ 38 , 39 ]. We have also recently found that several placental membrane proteins responsible for the transport of nutrients and xenobiotics are differentially expressed in the CTB and STB stages [ 33 ]. Here, we show that the expression of key monoamine transporters (SERT, NET, and DAT) is significantly altered during, and after, placental cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the trophoblast differentiation process is associated with simultaneous induction and repression of numerous genes that encode functionally related proteins [ 38 , 39 ]. We have also recently found that several placental membrane proteins responsible for the transport of nutrients and xenobiotics are differentially expressed in the CTB and STB stages [ 33 ]. Here, we show that the expression of key monoamine transporters (SERT, NET, and DAT) is significantly altered during, and after, placental cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Expression levels of the following genes were estimated: NET/SLC6A2 (Hs00426573_ m1), DAT/SLC6A3 (Hs00997374_m1), SERT/SLC6A4 (Hs00984349_m1), OCT3/SLC22A3 (Hs01009571_m1), and hCG/CGB3 (Hs00361224_gH). For this, transcripts of the genes were amplified in triplicate, using thermal programs recommended by the manufacturer, and quantified by the ΔΔCt method with YWHAZ Vachalova et al Reproductive Biology and Endocrinology (2022) 20:112 (Hs01122445_g1) and B2M (Hs00187842_m1) as reference genes, as previously described [33].…”
Section: Reverse Transcription and Gene Expression Analysismentioning
confidence: 99%
“…Various ABC transporters have been identified in the placenta and their localization and function at the maternal–fetal interface across gestation has been studied [ 35 ]. It is well-known that alterations in the expression of these transporters during different stages of gestation or due to ABC transporter modulators can lead to changes in the transfer of substrates to and from the fetus [ 9 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various ABC transporters have been identified in the placenta and their localization and function at the maternal-fetal interface across gestation has been studied [36]. It is well known that alterations in the expression of these transporters during different stages of gestation or due to ABC transporter modulators can lead to changes in the transfer of substrates to and from the fetus [9,37,38].…”
Section: Discussionmentioning
confidence: 99%